Implementasi Metode Pembelajaran Spot Capturing Pada Materi Pemanasan Global untuk Meningkatkan Keterampilan Proses Sains - Kiki Septaria; Binar Ayu Dewanti; Muhammad Habibbulloh (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
The Implementation of Spot Capturing Learning Methods in Global Warming Materials to Improve Science Process Skills. This research aims to determine the implementation of Spot Caturing learning methods and to know the improvement of the student science process skills after the use of Spot Capturing learning methods on global warming topic. This study uses one group pretest - posttest design where the subjects in this study were a class of students from Department of Science Education, Faculty of Teacher Training and Education, Lamongan Islamic University in the first semester of the 2018-2019 academic year. Research data is obtained through observation methods and tests and then analyzed by descriptive analysis method. The results of the study showed the level of implementation learning using spot capturing method of study at the first meeting average score 3.8 with excellent criteria, second meeting average score 3.8 with excellent criteria and the third meeting of the average score 3.9 with excellent criteria. The results of N-gain calculations on the science process skills showed increases with the medium category on the aspect of formulating issues with score 0.6, compiling hypotheses with score 0.4, and identifying variables with score 0.6, whereas aspects high category N-gain is there is observing aspect with score 1.0, communicating the data with score 0.7, and concluding the data with score 0.9. These results show that there is increases in the science process skills of student using the Spot Capturing learning method.